Rare presentation of Eccrine Porocarcinoma - Giri, Piyush; Pokhrel, Shrinkhala; Pandey, Pratishtha; Khadka, Karuna; Kunwar, Sushma; Banstola, Laxman; Gurung, Narendra Vikram (Journal of Nepal Health Research Council, 2025)
Eccrine porocarcinoma is a tumor of the sweat gland that mostly develops from an existing benign eccrine poroma. It is a rare cutaneous malignancy with a high risk of metastasis and recurrence. Known to affect the elderly population in general with no gender discrepancy, it presents as an ulcerative mass commonly in the trunk or head/neck region. Definitive diagnosis is made by histopathological findings of peculiar pleomorphic cells with nuclear hyperchromasia and mitotic activity, surrounded by ductal lumen. The standard treatment is complete surgical excision with appropriate surgical margins; adequate work-ups to look for metastasis and timely follow ups for chances of recurrence. Here we report a case of an 82-year-old patient who presented at our department with a long-standing exophytic lesion in the head that rapidly started growing in the past few weeks. After excisional biopsy and histopathology, the diagnosis of Eccrine porocarcinoma was made.Keywords: Cutaneous; eccrine porocarcinoma; malignancy; rare.